Tuberculosis of the Parotid Gland - Vivek Gupta; Kiran Patankar; Archana Shinde; Charu Bhosale; Ajitey Tamhane (Case Reports in Radiology)
Parotid gland involvement is extremely rare, even in countries in which tuberculosis is endemic. Clinically, it usually presents as a slow-growing mass indistinguishable from a malignancy. On imaging too, tuberculosis of the parotid may mimic neoplasm. The diagnosis of parotid tuberculosis needs a high degree of clinical suspicion. This paper highlights the clinical presentation, imaging findings, and importance of FNAC in diagnosis of this rare entity.